OBJEK FOKALISASI DAN KETEGANGAN DALAM CERITA NARATIF ANAK - U’um Qomariyah (Jurnal Semantik, 2017)
Vocalization is the most important and difficult aspect to be explained in correlation with its role in evocating literary facts and also its term complexity for understanding a work. Mieke Bal explains his theory in three parts, namely fabula, story, and text. Vocalization includes in a story. The result description (1) by understanding a developing-set of events and accompanying dialogue, NAM is a narrative text. This novel is a kind of framing text (wrapped story in a story). (2) The vocalized objects, that are the characters and space presentation. (3) The existence of riddles and treatment is one of the tensions in the novel.